Anhidrosis in the Horse (Non-Sweaters)—What Do We Know? - Laura Patterson-Rosa; Martha F. Mallicote; Robert J. MacKay; Samantha A. Brooks (EDIS)
This 3-page document provides an overview of anhidrosis in horses, including symptoms and management tips. Written by Laura Patterson-Rosa, Martha F. Mallicote, Robert J. MacKay, and Samantha A. Brooks, and published by the UF/IFAS Department of Animal Sciences, October 2020.